2015
DOI: 10.1007/s00125-015-3788-0
|View full text |Cite
|
Sign up to set email alerts
|

Discrete associations of the GCKR variant with metabolic risk in a Chinese population: longitudinal change analysis

Abstract: Aims/hypothesis Glucokinase regulatory protein gene (GCKR) variant rs780092 is a novel genetic variant associated with serum triacylglycerol (TG) identified in a genome-wide association study in East Asians. We aimed to investigate associations of rs780092 with incident type 2 diabetes and dyslipidaemia, and the longitudinal changes in glucose and lipid levels. Methods A community-based prospective cohort study was conducted at baseline in 2008, including 5,613 non-diabetic participants (37% male, mean age 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies have found that polymorphisms in GCKR (rs780094) are associated with non-alcoholic fatty liver disease in multiple populations [22][23][24]. Evidence of an association between this variant and type 2 diabetes or metabolic risk has also been detected [25,26]. An exome-chip association analysis for circulating FGF21 levels in Chinese individuals found that the common missense variant of GCKR, rs1260326 (p.Pro446Leu), may influence FGF21 expression via its ability to increase glucokinase (GCK) activity [27].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that polymorphisms in GCKR (rs780094) are associated with non-alcoholic fatty liver disease in multiple populations [22][23][24]. Evidence of an association between this variant and type 2 diabetes or metabolic risk has also been detected [25,26]. An exome-chip association analysis for circulating FGF21 levels in Chinese individuals found that the common missense variant of GCKR, rs1260326 (p.Pro446Leu), may influence FGF21 expression via its ability to increase glucokinase (GCK) activity [27].…”
Section: Discussionmentioning
confidence: 96%
“…4(c)). Although this is the first study on the relationship between MTHFR and GDM by mediation analysis, a few studies have focussed on the association between genetic polymorphisms and metabolic disease through this analysis approach (32,33) . It highlights that mediation analysis is a powerful method to test a hypothetical causal chain where one variable affects a second variable and, in turn, that variable affects the third variable.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking status was classified as current (>6 months on a daily basis) or non‐current drinking. Smoking status was classified as current smoker (>6 months on a daily basis), past smoker (having smoked more than 100 cigarettes in one's lifetime, but not smoked in the past 6 months or longer), or non smoker . The short form of the International Physical Activity Questionnaire (IPAQ‐SF) was used to categorize physical activity in leisure time into three groups: walking and moderate‐intensity and vigorous‐intensity exercises.…”
Section: Methodsmentioning
confidence: 99%